Plant physiology and development - Taiz, Lincoln; Moller, Ian Max; Murphy, Angus; Zeiger, Eduardo (New York Sinauer Associates, 2023)
Plant Physiology and Development incorporates the latest advances in plant biology, making it the most authoritative and widely used upper-division plant biology textbook. Up-to-date, comprehensive, and meticulously illustrated, the improved integration of developmental material throughout the text ensures that Plant Physiology and Development provides the best educational foundation possible for the next generation of plant biologists"-- Provided by publisher.
Unit I: Plant cells -- Unit II: Transport and translocation of water and solutes -- Unit III: Biochemistry and metabolism -- Unit IV: Growth and development.
Includes bibliographical references and index.
Keywords: Plant physiology; Plants -- Development